Gambaran Pencegahan Stunting Di Indonesia: Studi Literatur - Hinonaung, Jelita Siska Herlina; Manoppo, Erick Johans (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The purpose of the study was to determine the description of stunting prevention in Indonesia based on a literature review.Methods: The research method used is a literature study. Data collection by searching for Indonesian-language articles on the Google Scholar database with a time span of 2020-2022. The keywords used are "stunting prevention". Each article was filtered using a prism diagram to obtain six articles.Results: The results show that stunting prevention has been carried out in the form of basic community sanitation (providing access to clean water, provision of latrines, provision of waste water disposal facilities, and waste disposal), health access (providing MCH and family planning services, providing health insurance for underprivileged residents, education and nutrition improvement for stunting toddlers, and early marriage), religious approaches, community empowerment, communication of health messages, food diversity, and supplementary feeding.Conclusion: Based on the literature review, it can be concluded that stunting prevention in Indonesia is basic community sanitation, access to health, religious approaches, community empowerment, communication of health messages, food diversity, and supplementary feeding.